2013
DOI: 10.1371/journal.pone.0065378
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Home-Based Cupping Massage Compared to Progressive Muscle Relaxation in Patients with Chronic Neck Pain—A Randomized Controlled Trial

Abstract: Chronic neck pain is a major public health problem with very few evidence-based complementary treatment options. This study aimed to test the efficacy of 12 weeks of a partner-delivered home-based cupping massage, compared to the same period of progressive muscle relaxation in patients with chronic non-specific neck pain. Patients were randomly assigned to self-directed cupping massage or progressive muscle relaxation. They were trained and asked to undertake the assigned treatment twice weekly for 12 weeks. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
92
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(100 citation statements)
references
References 27 publications
1
92
0
7
Order By: Relevance
“…Reduction of pain was found in three of the studies as a result of the relaxation intervention (Baird and Sands, 2004;Poole et al, 2007;Lauche et al, 2013), although the only one to show significant differences between study groups was Baird and Sands (2004). While all three applied the progressive muscle relaxation method, described by Jacobson (1938), the intervention delivered by Baird and Sands (2004) also included a personalised guided imagery relaxation script (Bowering et al, 2013).…”
Section: Pain Intensitymentioning
confidence: 98%
“…Reduction of pain was found in three of the studies as a result of the relaxation intervention (Baird and Sands, 2004;Poole et al, 2007;Lauche et al, 2013), although the only one to show significant differences between study groups was Baird and Sands (2004). While all three applied the progressive muscle relaxation method, described by Jacobson (1938), the intervention delivered by Baird and Sands (2004) also included a personalised guided imagery relaxation script (Bowering et al, 2013).…”
Section: Pain Intensitymentioning
confidence: 98%
“…A total of 27 studies were excluded, as they did not have sufficient data for inclusion. Of these, 10 randomized trials were included in the systematic review and meta-analysis (23,(26)(27)(28)(29)(30)(31)(32)(33)(34). The search strategy and method of study selection is defined in Figure 1.…”
Section: Studies Descriptionmentioning
confidence: 99%
“…All studies adopted a two-armed parallel group design. Changes of VAS as the primary outcome of study were reported in 5 trials (26,(28)(29)(30)32). Six trials calculated the change in the Neck disability index (NDI) (23,26,28,(30)(31)(32).…”
Section: Studies Descriptionmentioning
confidence: 99%
See 2 more Smart Citations